Seleksi Mutan Tanaman Lamtoro (Leucaena leucocephala cv. Tarramba) Tahan Kutu Loncat terhadap Lingkungan Kering pada Rumah Kaca: Mutant Selection of Lamtoro (Leucaena leucocephala cv. Tarramba) on Dry Environment in Green House - rini Anggriani; P D M H Karti; I Prihantoro (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2021)
Forage is the main source of feed for ruminants. Forage consists of two types, namely grass and legumes. Leguminosa is a type of forage as a source of protein. One type of legume that is well known by breeders in Indonesia is lamtoro (Leucaena leucocephala cv. Tarramba). This study was aimed to produce candidate mutants of lamtoro drought resistant to acid stress conditions. The experiment in this study used an unbalanced completely randomized design with 6 treatments of 740 different replications based on different sources of lamtoro plant mutants at different levels (P0: 0 n= 89, P1: 100 gy n= 82, P2: 200 gy n= 153, P3:300 gy n=120, P4: 400 gy n= 244, P5: 500 gy n= 52). Variables observed included plant height, number of stalks, leaf loss and stem diameter. The results showed that lamtoro plants irradiated with gamma rays at a level of 200 gy-500 gy were significantly higher than 100 gy irradiation at 10 and 12 days watering, but the diameter of the plants was larger at 100 gy irradiation. It can be watering intervals of 10 days and 12 days on the parameters of height and stem diameter showed that gamma rays irradiation of 400 gy resulted in dry-resistant lamtoro mutant candidates under acid stress condition. Key words: gamma rays, lamtoro mutant, watering interval